Scenario Testing of the Energy and Environmental Performance of “The Glasgow House” - Sharpe, Tim; Shearer, Donald (Buildings (Basel), 2014)
This paper describes the results from a 12-month study of two prototype low energy dwellings built for Glasgow Housing Association (GHA). The houses are intended for mainstream and social tenure within Glasgow and contain a range of energy reducing features including one house with a thermally heavy clay block wall and one house using a conventional timber frame and both houses have sunspaces, Mechanical Ventilation with Heat Recovery (MVHR), solar thermal system and low energy lighting. The dwellings have been subject to an innovative monitoring strategy by MEARU, whereby test occupants (students recruited from the School of Architecture) have been asked to inhabit the buildings for six two-week periods using occupancy ‘scripts’ that determine their internal behaviour. The scenarios thus simulate varying patterns of occupancy in both houses simultaneously and the performance of the houses can then been compared. Indications are that although the clay block house had a poorer thermal performance, it did have other qualitative advantages, and consumption differences could be eliminated by exploiting the thermal mass. The performance of the active systems, including the MVHR system, was found to be problematic, and specific scenarios were undertaken to explore the implications of this.